Tinjauan Yuridis Pelaksanaan Perjanjian Jual Beli Online Melalui Rekening Bersama (Rekber) Pada Situs Toko Media Kaskus - Trihastoto, Novan, Septarina Budiwati, S.H., M.H (2016)
The purpose of this study were: (1) Knowing the implementation of online purchase agreement through the Joint Account (Rekber) On Site Media Store Kaskus. (2) Know the legal protection for the parties in the purchase agreement online through the Joint Account (Rekber) On Site Media Store Kaskus. Based on the analysis we concluded that: (1) The sale and purchase agreement online via rekber at FJB Kaskus shall refer to the terms of a legal contract, namely Article 1313 and in accordance with Article 1320 of the Civil Code. (2) Legal protection for sellers and buyers who use the services rekber been regulated in Law No. 8 of 1999 on Consumer Protection that is on Article 4 concerning the rights of consumers, Article 5 on the obligations of consumers, among others follow the procedures for use of goods, acting in good faith to make purchases of goods and pay according to the agreement, Article 6 concerning the right businesses, and Article 7 of the obligations of businesses. While legal protection can be carried out by the DJ in case of problems related to the use of services rekber in sale and purchase transactions is doing the blocking of accounts that are proven in default.